Comparing Sound-Field Speech-Auditory Brainstem Response Components between Cochlear Implant Users with Different Speech Recognition in Noise Scores - Jarollahi, Farnoush; Valadbeigi, Ayub; Jalaei, Bahram; Maarefvand, Mohammad; Motasaddi Zarandy, Masoud; Haghani, Hamid; Shirzhiyan, Zahra (Iranian Journal of Child Neurology, 2022)
Objectives Many studies have suggested that Cochlear Implant (CI) users vary in terms of speech recognition in noise. Studies in this field attribute this variety partly to subcortical auditory processing. Since study on speech-Auditory Brainstem Response (speech-ABR) provides good information about speech processing, so this work was designed to compare speech-ABR components between two groups of CI users with good and poor speech recognition in noise scores. Materials & Methods The present study was conducted on two groups of CI users aged 8-10 years old. The first group (CI-good) consisted of 15 children prelingual CI users who had good speech recognition in noise performance. The second group (CI-poor) matched with the first group, but they had poor speech recognition in noise performance. The speech-ABR test in a sound-field presentation was performed for all the participants. Results The speech-ABR response showed more delay in C, D, E, F, O latencies in CI-poor than CI-good users (P <0.05), meanwhile no significant difference was observed in initial wave (V(t= -0.293, p= 0.771 and A(t= -1.051, p= 0.307). Analysis in spectral-domain showed a weaker representation of fundamental frequency as well as the first formant and high-frequency component of speech stimuli in the CI-poor users. Conclusions Results revealed that CI users who showed poor auditory performance in noise performance had deficits in encoding of periodic portion of speech signals at brainstem level. Also, this study could be as physiological evidence for poorer pitch processing in CI users with poor speech recognition in noise performance.